Wi-Fi Long Distance Maritime Communications Data Analytics - José Eduardo da Silva Timóteo de Carvalho (2018)
Nowadays, wireless communications are becoming more and more important to the development of the society, not only in land, but also in the sea. When discussing about communications in maritime environments the scenario is different and harder, because of several factors, such as, the movement on the surface of the sea, the characteristics of the radio propagation and the possible intermittent obstruction that decrease the efficiency of signal propagation. Plenty of wireless communications solutions are already used in maritime environment, such as HF/VHF, which doesn't support high rates; satellite communications, which is an expensive technology and not affordable by most of users; and mobile communications (GSM, 3G and LTE), that only ensure connection near the coast. The main purpose of this dissertation is to contribute to the characterization of the propagation channel and the problems associated with the use of Wi-Fi technology for different frequencies in this kind of environment.